1995
DOI: 10.1063/1.114440
|View full text |Cite
|
Sign up to set email alerts
|

Manganese doped zinc sulphide nanoparticles by aqueous method

Abstract: Zinc sulphide nanoparticles in the size range ∼10–40 Å diameter have been synthesized using the aqueous chemical method. Scanning tunneling microscopy showed that particles are indeed nanosize particles. The size dependent band gap could be varied from a bulk value of 3.68 to 4.5 eV. X-ray diffraction indicated that nanoparticles are crystalline except for those with band gap ∼4.5±0.1 eV. Nanoparticles with particle size ∼21×2 Å diameter or energy gap 4.1×0.1 eV were doped with manganese. The photoluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(76 citation statements)
references
References 0 publications
5
59
3
Order By: Relevance
“…In contrast to what has been published before [2][3][4] no concentration quenching was observed. Previous reports stated that concentration quenching was observed at Mn 2+ concentrations of 0.12 at% Mn [3] and 1 at% Mn [4] incorporated in the nanoparticle.…”
Section: Influence Of the Mn 2+ Concentrationcontrasting
confidence: 55%
See 2 more Smart Citations
“…In contrast to what has been published before [2][3][4] no concentration quenching was observed. Previous reports stated that concentration quenching was observed at Mn 2+ concentrations of 0.12 at% Mn [3] and 1 at% Mn [4] incorporated in the nanoparticle.…”
Section: Influence Of the Mn 2+ Concentrationcontrasting
confidence: 55%
“…Previous reports stated that concentration quenching was observed at Mn 2+ concentrations of 0.12 at% Mn [3] and 1 at% Mn [4] incorporated in the nanoparticle. Possibly, the earlier reported decrease in quantum efficiency with increasing Mn content was not due to the increase Mn-concentration, but to other factors which influence the quantum efficiency (e.g.…”
Section: Influence Of the Mn 2+ Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Maity and Chattopadhyay [18] found an optimal Mn +2 concentration of 0.07%. Khosravi et al [19] observed a maximum luminescence at a doping concentration of 0.12 wt%. Leeb et al [20] reported an optimal Mn +2 concentration of 1%.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper they have measured PL emission for various excitation wavelengths. They observed a broad peak at about 363 nm (3.41 eV) for all samples in the PL spectra for all organic passivating agents at 220 nm excitation wavelength [2].…”
Section: Synthesis Overviewmentioning
confidence: 99%